Giant leiomyosarcoma of the rectum with lymph node metastasis: A case report and review of the literature. (2017) - Anzai, Hiroyuki; Nozawa, Hiroaki; Tanaka, Junichiro; Yasuda, Koji; Otani, Kensuke; Nishikawa, Takeshi; Tanaka, Toshiaki; Kiyomatsu, Tomomichi; Hata, Keisuke; Kawai, Kazushige; Ushiku, Tetsuo; Ishihara, Soichiro; et al.
Highlights: The most definitive feature of LMS is immunohistochemical positivity for desmin and SMA, and negativity for DOG 1, CD34, S-100 protein, and c-kit. It is crucial to diagnose leioyosarcoma precisely based on immunohistochemistry, and thereby distinguish it from GIST. Lymphadenectomy appears to be important for high-risk LMSs to perform R0 resection. Abstract: Introduction: Leiomyosarcoma of the gastrointestinal tract is very rare, with a reported frequency of less than 0.1% of all malignancies of the colorectum. It is important to diagnose leiomyosarcoma definitively by immunohistochemical profiling of smooth muscle actin, desmin, and CD34. True leiomyosarcoma of the colorectum diagnosed by immunnohistochemical profiling is extremely rare that only 13 reports have been published in reviews of resected gastrointestinal mesenchymal tumors after 1998. In addition, lymph node involvement is rare in patients with leiomyosarcoma. Herein we report an aggressive case of LMS in a rectosigmoid lesion with lymph node metastasis. Case presentation: A 76-year-old woman visited our hospital complaining of intermittent anal bleeding that had lasted 5 months. Image studies aiming at examining the cause of her anal bleeding revealed a tumor located between the right ovary, uterus, and the rectosigmoid. Histopathology of biopsied materials from the colonoscopy suggested a malignant tumor of mesenchymal origin. Surgical resection was performed with curative intent. The tumor was diagnosed as leiomyosarcoma by pathological examination. Moreover, one of the 31 regional lymph nodes retrieved was metastasized by leiomyosarcoma. Eight months later, follow-up CT scans revealed multiple recurrent lesions in the liver and peritoneum. Despite systematic chemotherapy, she deceased 12 months after the surgery. Conclusion: It is crucial to diagnose leioyosarcoma precisely based on immunohistochemistry, and thereby distinguish it from GIST. Although lymph node metastasis is rare, lymphadenectomy appears to be important for high-risk LMSs to perform R0 resection. Further investigation on leiomyosarcoma cases so far is required to establish standard treatment strategies.